Establishment of a new shrimp family Chlorotocellidae for four genera previously assigned to Pandalidae (Decapoda, Caridea, Pandaloidea) - Komai, T; Chan, T; De Grave, S (Pensoft Publishers, 2019)
A new caridean shrimp family, Chlorotocellidae, is established to accommodate four genera previously assigned to Pandalidae, viz., Chlorotocella Balss, 1914 (type genus), Chlorocurtis Kemp, 1925, Anachlorocurtis Hayashi, 1975, and Miropandalus Bruce, 1983, which represents the sister clade to a clade consisting of all other pandalid genera (including the two genera previously assigned to Thalassocarididae) in a recent comprehensive phylogenetic analysis of Pandaloidea. Diagnoses are provided for the new family and its constituent genera, and a comparison with Pandalidae is provided, for which a new diagnosis is given.